Analisis Determinan Dating Violence dalam Perspektif Lifestyle Exposure Theory - Ananda Putri Jayanti; Lucky Nurhidayanto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Dating violence is a form of interpersonal violence that includes physical, emotional, verbal, and sexual abuse, and is increasingly prevalent especially among teenagers and young adults. This research aims to analyze the determinant factors that influence the occurrence of dating violence using the Lifestyle Exposure Theory approach. This theory states that an individual's lifestyle and social activities can increase exposure to situations or perpetrators of violence. Lifestyles such as involvement in environments that are permissive of aggressive behavior, the use of addictive substances, relationships with minimal healthy boundaries, and a lack of social support are believed to contribute to the likelihood of violence in romantic relationships. This research uses a descriptive qualitative approach with a case study method. Data were collected through document analysis, in-depth interviews, and a literature review related to dating violence. The focus of the analysis is directed at two main stages of dating violence: internal factors and external factors. Social, psychological, and behavioral dimensions in Lifestyle Exposure Theory are used to understand the motives and patterns of the perpetrator's actions. This finding affirms that the risk of becoming a victim of violence is not only determined by internal factors but also by the exposure resulting from the lifestyle lived. Therefore, prevention interventions should focus on education about healthy relationships, enhancing emotional literacy, and fostering a lifestyle that supports safety and well-being in relationships.